6 is of course a multiple of 6, so you need only focus on
.
When n = 1, this expression has a value of 2 - 3 + 1 = 0, which is indeed a multiple of 6 (and any natural number for that matter).
Assume that 6 divides
.
Now,
![2(k+1)^3 - 3(k+1)^2 + (k+1) = (2k^3 + 6k^2 + 6k + 2) - (3k^2 + 6k + 3) + (k + 1) \\\\ = 2k^3 + 3k^2 + k \\\\ = 2k^3 - 3k^2 + k + 6k](https://img.qammunity.org/2022/formulas/mathematics/high-school/8zhpmmx8mcbx7xprwpvm27ubk73gomkn8n.png)
and this is divisible by 6. (6k is obviously a multiple of 6; that 6 divides the other three terms is due to the induction hypothesis.)